Randomized controlled trial for the efficacy of three versus five sessions of grief counseling on the psychological aspects following COVID-19 bereavement: A study protocol - Hajebi, Ahmad; Rasoulian, Maryam; Fathi, Marjan; Tiyuri, Amir; Abbasinejad, Maryam; Naserbakht, Morteza; Asadi, Ali; Khademoreza, Nooshin (Frontiers in Psychiatry, 2022)
Background: During the COVID-19 pandemic, many people have experienced traumatic losses and therefore are at risk of developing complicated grief, regarding the restrictions for the performance of routine mourning rituals. This study is a randomized controlled trial for assessing the efficacy of three versus five sessions of grief counseling on grief intensity, psychological distress and quality of life of grief among bereaved people due to COVID-19. Methods: A total of 120 bereaved people due to COVID-19, will be enrolled in this multi-center randomized controlled trial after assessment for inclusion and exclusion criteria. Following the informed consent procedure, participants will be allocated into two groups equally by the Stratified Balanced Block Randomization, one of them delivering a three-session and the other delivering a five-session grief counseling intervention. The intervention will be delivered by trained psychologists via in-person individual sessions. The primary outcome is grief intensity and the secondary outcomes are psychological distress, quality of life and satisfaction of the participants. These outcomes will be measured by the Grief Intensity Scale, General Health Questionnaire-28, the Short Form Health Survey-12, and the Client Satisfaction Questionnaire respectively. Assessments will be done at three time points, one before the intervention, and the others one month and three months after the intervention. The data will be analyzed using SPSS V.18 and Stata V.11 software. The analysis approach will be ‘Intention to Treat’. Discussion: Results of this study can be applied for selecting the most suitable intervention leading to prevention of complicated grief and maintenance and promotion of the mental health of bereaved people due to COVID-19.